Structure of Feeling and Digital Alienation: Cultural Materialism in Okky Madasari's Novel "Kerumunan Terakhir" - Riska Yunita; Else Liliani; Rio Mardani Suhardi (JENTERA: Jurnal Kajian Sastra, 2026)
This study aims to analyze Okky Madasari's novel Kerumunan Terakhir (2016) through the concepts of cultural materialism and Raymond Williams' (1977) structure of feelings in order to reveal the dynamics of digital alienation and identity precarity experienced by urban subjects in the social media era. This research is a qualitative study with a descriptive-analytical approach. The data are in the form of textual units, including dialogue excerpts, internal monologues, and narrative descriptions, sourced from the novel as the main data source. Data collection was carried out through a literature study with repeated reading techniques and corpus recording, while the analysis used the triple hermeneutics method that integrates literary analysis with critical media studies and affect theory. The results show that Madasari's narrative articulates the structure of emergent feelings through the duality of the novel's characters: Jayanegara, who is a nobody in the real world, transforms into @Matajaya, who is adored on social media; and Noname, who lives in a remote village, transforms into the influential @Akardewa, a manifestation of digital alienation, the precarity of virtual identity, and the subject's inability to separate their real self from their digital persona. This study concludes that Indonesian fiction functions as an archive of digital social experiences that have not been formally articulated and demonstrates the transnational relevance of Williams's theory in the context of the Digital Global South. Abstrak Penelitian ini bertujuan menganalisis novel Kerumunan Terakhir (2016) karya Okky Madasari melalui konsep materialisme budaya dan struktur perasaan Raymond Williams (1977) guna mengungkap dinamika alienasi digital dan prekaritas identitas yang dialami subjek urban di era media sosial. Penelitian ini merupakan penelitian kualitatif dengan pendekatan deskriptif-analitis. Data berupa satuan tekstual mencakup kutipan dialog, monolog internal, dan deskripsi naratif yang bersumber dari novel sebagai sumber data utama. Pengumpulan data dilakukan melalui studi pustaka dengan teknik pembacaan berulang dan pencatatan korpus, sedangkan analisis menggunakan metode triple hermeneutics yang mengintegrasikan analisis sastra dengan kajian studi media kritis dan teori afek. Hasil penelitian menunjukkan bahwa narasi Madasari mengartikulasikan struktur perasaan emergen melalui dualitas tokoh-tokoh novel Jayanegara yang bukan siapa-siapa di dunia nyata menjelma menjadi @Matajaya yang dipuja di media sosial; Noname, yang hidup di perdesaan terpencil, menjelma menjadi @Akardewa yang berpengaruh sebagai manifestasi dari alienasi digital, prekaritas identitas virtual, dan ketidakmampuan subjek memisahkan diri nyata dari persona digitalnya. Studi ini menyimpulkan bahwa fiksi Indonesia berfungsi sebagai arsip pengalaman sosial digital yang belum terartikulasikan secara formal dan mendemonstrasikan relevansi teori transnasional Williams dalam konteks Global South Digital.